KAMBİYO SENETLERİNDE BEYAZ CİRO - (:unkn) unknown (My University, 2017)
Emre yazılı kambiyo senetlerinde yer alan hakkın devri ciro ve senedinteslimi ile gerçekleşmektedir. Ciro, şekil bakımından üç türlü gerçekleşmektedir. Tamciroda senedin devredildiği şahıs belli iken, beyaz ciroda belli değildir. Bu anlamdabeyaz ciro senedin hamiline yazılı senetmiş gibi tedavül etme olanağı sağlar. Bu çalış-mada, beyaz cironun şekil şartları, farklı ciro türlerinin (özellikle tahsil ve rehin cirosu-nun) beyaz ciro şeklinde yapılıp yapılamayacağı ve beyaz cironun hükümleri ele alın-mıştır. Çalışmamızda ayrıca, senedin arkasında veya ön yüzünde yer alan ve fakat cirozincirine dâhil edilemeyen imzanın Alman Hukukunda kabul edildiği gibi, garanti ciro-su olarak değerlendirilip değerlendirilemeyeceğine de değinilmektedir.

The receivable right which is fully bounded in negotiable instruments to order can only be transferred with endorsement and handing over the instrument. The form of endorsement can be divided in three parts. According to the endorsement in full, the person who was taken the instrument by the endorsement can be designated. On the other hand, in accordance with the blank endorsement is not possible. In this manner, the blank endorsement provides to circulate the instrument like bearer instrument. In this study, it was considered that if the form conditions of blank endorsement and different type of endorsement (especially endorsement for collection and pawn) can be considered as blank endorsement. The effects of blank endorsements were also considered. In addition to this it was also mentioned in our study that, if the signature which is behind or front of endorsement (but outside the chain) is valid as guarantee endorsement (as it is in German law) or not.
Das Blankoindossament
Keywords: Hukuk